Big Power Game in the South China Sea - Poh, Angela (2015)
US naval manoeuvres and Chinese activities in the South China Sea reflect a new big power game in which regional countries are caught in the middle. ASEAN members need to stay united to overcome the pressures from both powers, before the South China Sea truly turns into a playground for the giants.